The Effect of General Anesthesia vs. Regional Anesthesia on Postoperative Delirium—A Systematic Review and Meta-Analysis - Zhu, Xianlin; Yang, Min; Mu, Junying; Wang, Zaiping; Zhang, Liang; Wang, Hongbai; Yan, Fuxia (Frontiers in Medicine, 2022)
Background: Postoperative delirium (POD) commonly occurs in patients following major surgeries, and is associated with adverse prognosis. The modes of anesthesia may be associated with POD occurrence. General anesthesia (GA) causes the patient loss of consciousness by altering the levels of some neurotransmitters as well as signaling pathways. We conducted this meta-analysis to investigate the effect of GA versus regional anesthesia (RA) on POD incidence in surgical patients. Methods: The databases of Pubmed, Embase and Cochrane Library were searched till 22nd Oct 2021. The eligible criteria were participants aged 18 years or older, patients undergoing surgery under GA and RA; and articles reporting the effect of GA versus RA on POD incidence. RevMan 5.3 was used to perform statistical analyses. Results: 21 relevant trials with a total of 1702151 patients were included. The pooled result using random-effects model with OR demonstrated significant difference in POD incidence between patients with GA and RA (OR = 1.15, 95% CI: [1.02, 1.31], I2 =83%, p for effect = 0.02). We did not obtain the consistent pooled result after sensitivity analysis (OR = 0.95, 95% CI: [0.83, 1.08], I2 =13%, p for effect = 0.44) and excluded the articles without the information on preoperative cognitive or neuropsychological assessmen (OR = 1.12, 95% CI: [1.00, 1.25], I2 =80%, p for effect = 0.05), respectively. Conclusion: This meta-analysis could not identify that GA was significantly associated with POD occurrence in the surgical patients compared with RA.